ORGANIZATIONAL AND LEGAL PROBLEMS OF POPULATION’S PARTICIPATION IN LOCAL SELF - Zhanuzakova Лейла Тельмановна (Scientific and legal journal «Bulletin of the Institute of Legislation and Legal Information of the Republic of Kazakhstan», 2013)
In the article are considered issues of administrative-territorial units population’s participation in the local self-government. Based on the analysis of the current legislation are made proposals for involving citizens in the process of solving local importance problems.